Prevalence and correlates of smoking and nicotine dependence: results of a nationwide cross-sectional survey among Singapore residents. Issue 10 (18th October 2019) - Shahwan, Shazana; Abdin, Edimansyah; Shafie, Saleha; Chang, Sherilyn; Sambasivam, Rajeswari; Zhang, Yunjue; Vaingankar, Janhavi Ajit; Teo, Yik Ying; Heng, Derrick; Chong, Siow Ann; Subramaniam, Mythily
Abstract : Background: Since the Singapore Mental Health Study in 2010 which reported a 16.0% prevalence rate for current smokers and 4.5% for nicotine dependence, new anti-smoking strategies have been implemented. The aim of this study was to compare smoking trends from the 2010 study with the second Singapore Mental Health Study in 2016 (SMHS 2016). Methods: A survey of 6126 individuals aged 18 years and above randomly selected among Singapore residents was conducted using the same methodology as the 2010 study. The measures used in this analysis were sociodemographic questions, the Composite International Diagnostic Interview which assessed for psychiatric disorders, the Fagerstrom Test for Nicotine Dependence and a list of chronic physical conditions that were prevalent in Singapore. Logistic regression analyses were used to test for associations between smoking/nicotine-dependence and other measures. Results: In the SMHS 2016, 16.1% were current smokers and 3.3% were nicotine-dependent. As compared with non-smokers, current smokers were more likely to be younger, male gender, of ethnic minority and had lower/vocational education level. Younger age, male gender, lower/vocational education and psychiatric disorders (major depression, bipolar disorder and alcohol use disorders) predicted nicotine dependence. No associations were found between nicotine dependence and any of the chronic conditions. Conclusion: The prevalence of current smokers in the population has plateaued while that of nicotine dependence has decreased from 2010. However, the study did not investigate the use of e-cigarettes. Inequalities in smoking and nicotine dependence continue to pervade the population particularly among those of ethnic minority, lower/vocational education and the mentally ill.